(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The personnel reserve plays an important role in the formation and renewal of the political elite. The Republic of Kazakhstan and the Russian Federation share historically determined features of the creation and functioning of the highest bureaucratic apparatus, which takes or has an exclusive influence on state decision-making. The purpose of the study was to learn and compare the mechanism of formation of the personnel reserve in Kazakhstan and Russia. In order to structure and analyze the features of the personnel reserve a number of criteria have been developed: implementation levels, age priorities, specialization, effectiveness, and others. The results of the study showed that the mechanisms for forming the personnel reserve of Kazakhstan and Russia are largely similar, have the same, politically determined, reasons for creation and implementation period. However, there are also differences; Kazakhstan focuses on the promotion of young leaders and forms a common reserve that does not take into account the area of management. Russia is expanding the age limits of reservists and introducing specialized personnel reserves. The analysis of the experience of both countries makes it possible to identify promising areas for improving the mechanisms of the personnel reserve. Key words: personnel reserve, political elite, recruitment, career, personnel promotion.